2018
DOI: 10.1186/s13024-018-0257-5
|View full text |Cite|
|
Sign up to set email alerts
|

Inoculation of α-synuclein preformed fibrils into the mouse gastrointestinal tract induces Lewy body-like aggregates in the brainstem via the vagus nerve

Abstract: Abstract:BackgroundIntraneuronal α-synuclein (α-Syn) aggregates known as Lewy bodies (LBs) and the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) are the pathological hallmarks of Parkinson’s disease (PD). Braak’s hypothesis based on autopsy studies suggests that Lewy pathology initially occurs in the enteric nervous system (ENS) and then travels retrogradely to the dorsal motor nucleus of the vagus nerve (dmX), proceeding from there in a caudo-rostral direction. Recent evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
196
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 47 publications
3
196
3
2
Order By: Relevance
“…The present finding of robust and extensive gut-to-brain asyn propagation contrasts with two recent reports [25, 52]. In those studies, asyn PFFs were injected directly into the stomach or colon of mice, rats, and macaques, but little or no persisting asyn pathology was seen in the brainstem.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present finding of robust and extensive gut-to-brain asyn propagation contrasts with two recent reports [25, 52]. In those studies, asyn PFFs were injected directly into the stomach or colon of mice, rats, and macaques, but little or no persisting asyn pathology was seen in the brainstem.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, we did not see asyn pathology in the myenteric and submucosal plexus of the PFF-injected WT rats, which contrasts with the observed persistent enteric pathology in PFF-injected WT rodents and non-human primates [25, 52]. The absence of pathology in the present WT rats could be explained by a species barrier, since we used human asyn PFFs in the WT rats, whereas the previous studies used species-compatible PFFs.…”
Section: Discussioncontrasting
confidence: 72%
“…After 12 months, pS129‐positive inclusions were detected throughout the brain in connected areas, including the SNpc. However, there was no further progression of Lewy body‐like pathology at 23 months when pS129 was propagation studied after injecting PFFs into the mouse gastric wall (Rey et al., ; Uemura et al., ). The study demonstrated formation of pS129‐positive aggregates in the dorsal motor nucleus of the vagus nerve, which could be prevented by vagotomy.…”
Section: Alpha‐synuclein Overexpression Modelsmentioning
confidence: 99%
“…PD-like pathology has been observed in peripheral neurons at many anatomically distinct sites including the colon (Lebouvier et al 2010) and vermiform appendix (Killinger et al 2018). From these sites, peripheral pathology could then spread to the DMNV through vagus nerve afferents and efferents, effectively seeding the pathological process of PD (Holmqvist et al 2014;Uemura et al 2018). However, results from several studies suggest that the progressive spread of pathology from the peripheral sites to higher brain structures is either rare or unlikely (Holmqvist et al 2014;Uemura et al 2018).…”
Section: Cellular and Molecular Factors Promote The Spread Of A-syn Pmentioning
confidence: 99%
“…However, results from several studies suggest that the progressive spread of pathology from the peripheral sites to higher brain structures is either rare or unlikely (Holmqvist et al 2014;Uemura et al 2018). Peripherally injected PFFs into the mouse gastric wall results in pathology in the DMNV (Holmqvist et al 2014;Uemura et al 2018) but this pathology doesn't progressively spread through the CNS Peripheral asyn seeds can accelarate widespread CNS pathology in transgenic mice harboring a aggregation prone pathological variant of a-syn (Sacino et al 2014a). a-Syn aggregates injected into peripheral sites are most likely transported intracellularly to the brain via axonal transport (Freundt et al 2012;Holmqvist et al 2014;Sacino et al 2014a).…”
Section: Cellular and Molecular Factors Promote The Spread Of A-syn Pmentioning
confidence: 99%